Roles of ROS and cell cycle arrest in the genotoxicity induced by gold nanorod core/silver shell nanostructure - Wang, Dan; Dan, Mo; Ji, Yinglu; Wu, Xiaochun; Wang, Xue; Wen, Hairuo (Nanoscale research letters, 2020)
To understand the genotoxicity induced in the liver by silver nanoparticles (AgNPs) and silver ions, an engineered gold nanorod core/silver shell nanostructure (Au@Ag NR) and humanized hepatocyte HepaRG cells were used in this study. The involvement of oxidative stress and cell cycle arrest in the DNA and chromosome damage induced by 0.4–20 µg mL −1 Au@Ag NR were investigated by comet assay, γ-H2AX assay and micronucleus test. Further, the distribution of Au@Ag NR was analyzed. Our results demonstrated that both Ag + and Au@Ag NR led to DNA cleavage and chromosome damage (clastogenicity) in HepaRG cells and that the Au@Ag NR retained in the nucleus may further release Ag + , aggravating the damages, which are mainly caused by cell cycle arrest and ROS formation. The results reveal the correlation between the intracellular accumulation, Ag + ion release and the potential genotoxicity of AgNPs.